Efektivitas Biofungisida Jamur Trichoderma harzianum dan Trichoderma koningii dengan Berbagai Dosis terhadap Intensitas Serangan Penyakit Layu Jamur Fusarium dan Pertumbuhan Vegetatif pada Tanaman Cabai Merah (Capsicum annum L.) - Sadin, Yuliana Ivantri; Marhaeni Julyasih, Ketut Srie; Manalu, Jean Nihana (JURNAL AGROPLASMA, 2025)
This study focuses on controlling Fusarium wilt disease in red chili plants, a common horticultural crop in Indonesia. The disease caused by Fusarium pathogens poses challenges to farmers. An alternative control method is the use of biofungicides derived from fungi Trichoderma harzianum and Trichoderma koningii. The research was conducted at two different locations, including the isolation of Fusarium pathogens and identification of  Trichoderma fungi. The multiplication of  T. harzianum and  T. koningii was carried out on a rice medium at the Agensia Hayati / Botanical Pesticide Laboratory in Biaung. Seedling planting and biofungicide application took place at the Agensia Hayati Laboratory field, Jalan Tegal Harum, Gang Sakura, Biaung, East Denpasar District, Denpasar City, Bali, from May to August 2025.The experimental design used was a Completely Randomized Design (CRD) with 7 treatments and 5 replications. Treatments included a control (0 grams) and biofungicide doses of 10, 20, and 30 grams for both T. harzianum and T. koningii. Statistical analysis using one-way ANOVA showed significant differences (p<0.05) among treatments in reducing Fusarium wilt disease intensity. The highest dose of 30 grams of both biofungicides was the most effective, achieving 100% disease suppression 28 days after treatment. Additionally, the biofungicide application showed significant effects on the number of leaves at 7 days after treatment and plant height at 28 days after treatment. These results indicate that biofungicides from T. harzianum and T. koningii can be used as an environmentally friendly and sustainable alternative to control Fusarium wilt in red chili plants. Keywords: Fusarium Wilt, red chili pepper, Trichoderma harzianum, Trichoderma koningii